Highly Sensitive Sensing of NO and NO2 Gases by Monolayer C3N. Issue 6 (17th April 2018) - Babar, Vasudeo; Sharma, Sitansh; Schwingenschlögl, Udo
Abstract: Using density functional theory with van der Waals dispersion correction, the adsorption behavior of common gaseous pollutants (CO, NO, NO2, and NH3 ) on monolayer C3 N is investigated. The adsorption sites and energies, binding distances, charge transfers, and electronic band structures are calculated to understand the influence of the adsorbed molecules on the transport properties of monolayer C3 N. The current–voltage characteristics are calculated using the nonequilibrium Green's function formalism. It turns out that all investigated molecules are physisorbed on monolayer C3 N and that NO and NO2 gases can be sensed with high sensitivity. The recovery time of the sensor is found to be outstanding in the case of NO sensing (2.4 μs at room temperature) and competitive to other materials in the case of NO2 sensing. Abstract : NO and NO2 gases are sensed by monolayer C3 N with very high sensitivity. An outstandingly short recovery time of the material, even at room temperature, is found in the case of NO sensing, giving rise to an unprecedented combination of favorable material properties that opens great application potential.